MONITORING THE ECOLOGICAL CONDITION OF ARAL SEA PASTURES BASED ON GIS TECHNOLOGIES AND DRONES - Oteniyazov Dauletbay Orinbay uli (International Journal of Literature and Language Studies, 2026)
The ecological degradation of pastures in the Aral Sea region has become a major environmental and socio-economic concern due to desertification, soil salinization, vegetation loss, and climate change impacts. Traditional methods of pasture assessment are often time-consuming, labor-intensive, and limited in spatial coverage. Recent advances in Geographic Information Systems (GIS) and unmanned aerial vehicles (UAVs), commonly known as drones, have provided new opportunities for efficient environmental monitoring. This study examines the application of GIS technologies and drones for assessing the ecological condition of pastures in the Aral Sea region. GIS enables the integration, analysis, and visualization of spatial data obtained from satellite imagery, field surveys, and drone observations. Drones equipped with high-resolution cameras and multispectral sensors allow detailed monitoring of vegetation cover, biomass productivity, soil salinity, and land degradation processes.